2014
DOI: 10.1261/rna.045005.114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the RNA recognition element of the RBPMS family of RNA-binding proteins and their transcriptome-wide mRNA targets

Abstract: Recent studies implicated the RNA-binding protein with multiple splicing (RBPMS) family of proteins in oocyte, retinal ganglion cell, heart, and gastrointestinal smooth muscle development. These RNA-binding proteins contain a single RNA recognition motif (RRM), and their targets and molecular function have not yet been identified. We defined transcriptome-wide RNA targets using photoactivatable-ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) in HEK293 cells, revealing exonic mature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 53 publications
(61 reference statements)
6
78
0
Order By: Relevance
“…With this approach, we identified 196 mRNAs (corresponding to 186 individual genes) whose stability was most significantly increased in the absence of ERG (Fig. 4a, green 36 , we found that these ERG degradation targets were strongly enriched in RBPMSassociated mRNAs, thus supporting a functional role for RBPMS in ERG-mediated decay (Fig. 4b).…”
Section: Erg Rbpms and Cnot2 Promote Degradation Of Mitotic Mrnasmentioning
confidence: 75%
See 1 more Smart Citation
“…With this approach, we identified 196 mRNAs (corresponding to 186 individual genes) whose stability was most significantly increased in the absence of ERG (Fig. 4a, green 36 , we found that these ERG degradation targets were strongly enriched in RBPMSassociated mRNAs, thus supporting a functional role for RBPMS in ERG-mediated decay (Fig. 4b).…”
Section: Erg Rbpms and Cnot2 Promote Degradation Of Mitotic Mrnasmentioning
confidence: 75%
“…Strikingly, the set of ERG interactors identified in our Y2H screen also included RNA-binding Fox-1 (RBFOX1 or A2BP1) and RNA-binding protein with multiple splicing (RBPMS or Hermes), two RBPs with canonical RNA-recognition motifs 34,35 (Supplementary Table 1). Whereas RBFOX proteins are wellcharacterized splicing factors, the role of RBPMS in mRNA processing remains unclear 36,37 . From these findings, we hypothesized that ERG might be recruited to specific mRNAs through its interaction with RBPs including RBPMS.…”
Section: Erg Is Recruited To Mrna Via Its Interaction With Rbpsmentioning
confidence: 99%
“…Other resources have started to collect RNA interactions Hao et al 2016;Junge et al 2017;Yi et al 2017). However, new interactions are continuously published for yeast and mammalian mRNAs (Baltz et al 2012;Baejen et al 2014;Farazi et al 2014;Gerstberger et al 2014;Castello et al 2016b) and for less characterized classes of ncRNAs such as SUT, CUT, and XUT (Tuck and Tollervey 2013). We believe that it is extremely timely to begin to collate RNA interaction data from the literature and high-throughput experimental screens.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that Hermes is a repressor of nrp1 mRNA translation, either directly or indirectly, which controls Nrp1 expression temporally in RGC growth cones. Interestingly, the mammalian ortholog of Hermes, RBPMS2, has also been shown to bind to nrp1 mRNA (Farazi et al, 2014). …”
Section: Discussionmentioning
confidence: 99%